Al-Islām wa al-ʻIlm wa al-Taʻallum - Ahmad Abd. Rahim (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2003)
The first verse revealed by Allah SWT., is a command to read. Reading is a means to gain knowledge. This proves that Islam is very concerned with science and teaching. This paper describes the evidence of the statement above. Even further explore the close relationship between Islam, science and teaching.